STRATEGI BADAN PELAKSANA OTORITA DANAU TOBA (BPODT) DALAM MENARIK INVESTASI ASING DI KAWASAN DANAU TOBA - Sabrina, Dita Putri; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study analyzes the strategy of the Lake Toba Authority Implementing Agency (BPODT) in attracting Foreign Direct Investment (FDI) in the Lake Toba region as a Super Priority Tourism Destination. Government budget constraints and infrastructure challenges make FDI a strategic solution to accelerate the development of world-class tourism. This study uses a descriptive qualitative approach with a Liberalism and FDI Theory perspective at the state level. Data were collected through a documentary study from 2022 to 2024. BPODT implemented four strategic pillars: Image Development, Infrastructure Development, including the 386-hectare Toba Caldera Resort, Investor Facilitation through KSO/BGS/BSG schemes, and Investment Promotion through Indonesia-China bilateral forums. Research result show significant success with investment commitments totaling US400 million, an increase in foreign tourists from 200,000 (2022) to over one million (2024), and the restoration of UNESCO Global Geopark status, demonstrating the effectiveness of BPODT's strategy in creating a conducive investment climate for international investors. Keywords: BPODT, Foreign Investment, Lake Toba, Tourism, Infrastructure